Analisis Faktor-Faktor yang Memengaruhi Financial Satisfaction Pengguna E-Wallet - Amelia, May; Isbanah, Yuyun (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The research aims to determine the effect of financial literacy, financial strain, financial management behaviour, and income on financial satisfaction in the e-wallet user in Surabaya. The research is a type of conclusive causality research with quantitative research data using purposive sampling and snowball sampling techniques. The data collection instrument used in this research was the distribution of online questionnaires. The samples used in this research were 207 respondents from e-wallet user in Surabaya. The data analysis use Structural Equation Model (SEM) technique with AMOS tools. This research shows that only financial management behaviour influences financial satisfaction because of their good financial management awareness. Financial literacy has no financial satisfaction because the information is easy to get, but what is received is not necessarily correct. Financial strain has no influences on financial satisfaction because respondent did not experience financial strain, so most of them are college students and students. Income also has no influences on financial satisfaction because the income received still depends on each parent.